2020
DOI: 10.1093/bib/bbaa225
|View full text |Cite
|
Sign up to set email alerts
|

Molecular characterization, biological function, tumor microenvironment association and clinical significance of m6A regulators in lung adenocarcinoma

Abstract: N6-methyladenosine (m6A) modification can regulate a variety of biological processes. However, the implications of m6A modification in lung adenocarcinoma (LUAD) remain largely unknown. Here, we systematically evaluated the m6A modification features in more than 2400 LUAD samples by analyzing the multi-omics features of 23 m6A regulators. We depicted the genetic variation features of m6A regulators, and found mutations of FTO and YTHDF3 were linked to worse overall survival. Many m6A regulators were aberrantly… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
3
1
1

Citation Types

5
104
0

Year Published

2021
2021
2023
2023

Publication Types

Select...
7
1
1

Relationship

2
7

Authors

Journals

citations
Cited by 118 publications
(109 citation statements)
references
References 91 publications
5
104
0
Order By: Relevance
“…12 Recently, several bioinformatics studies have shown that the dysregulation of m 6 A regulators is involved in LUAD. 13,14 The specific role of m 6 A regulators in lncRNAs remains unclear; therefore, understanding the mechanism of m 6 A-related lncRNAs in the development of LUAD may be useful for prognostic targets.…”
Section: Introductionmentioning
confidence: 99%
“…12 Recently, several bioinformatics studies have shown that the dysregulation of m 6 A regulators is involved in LUAD. 13,14 The specific role of m 6 A regulators in lncRNAs remains unclear; therefore, understanding the mechanism of m 6 A-related lncRNAs in the development of LUAD may be useful for prognostic targets.…”
Section: Introductionmentioning
confidence: 99%
“…Research based on the heterogeneity of m 6 A regulators to identify distinct subtypes of sepsis (27), of which the GSEA and CIBERSORT analyses found different immunocompetent status (such as Th1 cells, T cells CD4 activated, NK cells activated and B cells activated) among subtypes and indicated the potential relation among m 6 A regulators and leukocyte infiltration. Studies also have shown that m 6 A regulators contribute to TME formation (28) and affect the abundance of TILs (29) as well as response to ICIs treatment (30).…”
Section: Introductionmentioning
confidence: 99%
“…Previous studies have shown that molecular heterogeneities are tightly associated with therapeutic outcomes and prognosis of patients in various cancer types [ 14 , 62 ], we wondered whether there were distinct molecular phenotypes in ESCC that contributed to patients' survival differences. To answer this question, we first screened all survival-related genes in GSE53625 and TCGA ESCC cohorts separately ( Fig.…”
Section: Resultsmentioning
confidence: 99%
“…With the continuous accumulation of data, researchers can now explore the key characteristics of diseases in a larger cohort based on appropriate data integration strategy and obtain more convincing results supported by multiple pieces of evidence [ 12 , 13 ]. Such strategies have been widely applied to study the molecular features of various cancer types such as lung adenocarcinoma, hepatocellular carcinoma, and gastric cancer [14] , [15] , [16] . However, compared with other common cancer types, such approaches were less applied to study the molecular features of ESCC.…”
Section: Introductionmentioning
confidence: 99%